Effect of Combination of Yoga, Naturopathy Medicine, and Herbs on Renal Functions and Quality of Life in Patients with Chronic Kidney Disease: A Pilot Study - Y. Deepa; A. Vijay; L. Nivethitha; Edmin Christa; N. Manavalan; A. Mooventhan (Indian Journal of Ayurveda and Integrative Medicine KLEU)
Background: Chronic kidney disease (CKD) is distinguished by abnormality in kidney structure or function that persists for over 3 months. It is a multifaceted condition that leads to impaired kidney function and can progress to end-stage kidney disease. Complementary and alternative medicine, such as yoga and naturopathy (YN), has demonstrated effectiveness in treating and preventing a number of conditions associated with CKD. This study aims to investigate the impact of YN on renal function and quality of life (QoL) in individuals with CKD. Materials and Methods: Twenty-six individuals diagnosed with CKD underwent YN-based lifestyle intervention for the period of 30 days. Assessments such as urea, creatinine, fasting blood sugar (FBS), postprandial blood sugar (PPBS), hemoglobin, and Kidney Disease Quality of Life 36-Item Short Form Survey (KDQOL-36) were done before and after the intervention. Results: Results of the study showed a significant reduction in urea, creatinine, FBS, and PPBS and a significant increase in hemoglobin levels and KDQOL-36 scores among study participants after the intervention period. Conclusion: YN-based lifestyle interventions help to improve renal functions and QoL in patients with CKD by reducing urea, creatinine, and blood glucose levels and by increasing Hb levels. However, the limited sample size and absence of a control group restrict the scope of this study. Hence, further randomized controlled trials with a larger sample size are recommended to validate the results of the study.